The infectious disease blood safety risk of Australian hemochromatosis donations. Issue 12 (23rd September 2016) - Hoad, Veronica; Bentley, Peter; Bell, Barbara; Pathak, Praveen; Chan, Hiu Tat; Keller, Anthony
Abstract : BACKGROUND: It has been suggested that blood donors with hereditary hemochromatosis may pose an increased infectious disease risk and adversely affect recipient outcomes. This study compares the infectious disease risk of whole blood (WB) donors enrolled as therapeutic (T) donors to voluntary WB donors to evaluate the safety of blood products provided by the T donors. STUDY DESIGN AND METHODS: This was a retrospective cohort study of all WB donations at the Australian Red Cross Blood Service who donated between January 1, 2011, and December 31, 2013, comparing a yearly mean of 11, 789 T donors with 107, 773 total donations and a yearly mean of 468, 889 voluntary WB donors with 2, 584, 705 total donations. We compared postdonation notification of infectious illnesses, bacterial contamination screening results, and positive tests for blood borne viruses in T and WB donors. RESULTS: Rates of transfusion‐transmissible infections in donations destined for component manufacture were significantly lower in therapeutic donations compared to voluntary donations (8.4 vs. 21.6 per 100, 000 donations). Bacterial contamination (43.0 vs. 45.9 per 100, 000 donations) and postdonation illness reporting (136.2 vs. 110.8 per 100, 000 donations) were similar in both cohorts. CONCLUSIONS: The Australian therapeutic venisection program enables T donors to provide a safe and acceptable source of donated WB that has a low infectious disease risk profile.